2018
DOI: 10.4103/ejd.ejd_63_18
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of microleakage in self-etch fissure sealants and conventional fissure sealants with total-etch or self-etch adhesive systems

Abstract: Objective:The present study was conducted to compare microleakage in self-etching fissure sealants and conventional fissure sealants with total-etch or self-etch adhesive systems.Settings and Design:This experimental in vitro study was conducted on 60 healthy third molars extracted from humans. The first group received Acid etch + Clinpro sealant, the second group received Acid etch + Single bond 2 + Clinpro sealant, the third group received Single bond universal (self-etching bonding) + Clinpro sealant, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 11 publications
1
21
1
Order By: Relevance
“…Our findings contrast with those of Nahvi et al [29]. They reported significant reduction in microleakage with the use of a pre-sealant bonding agent.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings contrast with those of Nahvi et al [29]. They reported significant reduction in microleakage with the use of a pre-sealant bonding agent.…”
Section: Discussioncontrasting
confidence: 99%
“…Results of present study showed no statistically significant difference in the microleakage scores between two groups. This is in well agreement with the findings of a study by Nahvi A et al (18), who compared self-etching sealant (Prevent seal) with conventional acid etch sealant with / without application of bonding agent. Findings of the later study showed prevent seal had comparable microleakage scores to conventional acid etch sealant (Clinpro) when applied without bonding agent.…”
Section: Discussionsupporting
confidence: 93%
“…The application of bonding agent after etching is still a controversy. The critics of the same put forth this as an time consuming additional step, which also increases the treatment cost (18). Long term follow up clinical studies by Mascarenhas et al (19) and Boksman et al (20), concluded that use of bonding agent before sealing does not improve the sealant retention in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Our findings contrast with those of Nahvi and colleagues. 29 They reported significant reduction in micro-leakage with the use of a pre-sealant bonding agent. Elsewhere, the bonding agent beneath the sealant was shown to increase the bond strength even in moisture-contaminated conditions, and to decrease micro-leakage.…”
Section: Discussionmentioning
confidence: 99%